Impact of medication review, within a shared decision-making framework, on deprescribing in people living in care homes. Issue 1 (20th December 2016) - Baqir, Wasim; Hughes, Julian; Jones, Tania; Barrett, Steven; Desai, Nisha; Copeland, Richard; Campbell, David; Laverty, Annie
Abstract : Objectives: The key objectives of this study were to quantify extent of prescribing, reasons for deprescribing, common therapeutic groups of medicines deprescribed and adverse events. Methods: A retrospective analysis was carried out on a quality improvement project where 422 care home residents in 20 care homes received a medicines optimisation review with a pharmacist and other members of the healthcare team (general medical practitioner, care home nurse). Data on number, type and cost of medicines were collected. Statistical analysis was performed to test for differences between pharmacist-only review and the pharmacist plus general practitioner (GP), and to identify any correlation between the original number of medicines and the number of medicines stopped. Results: Of the 422 patients reviewed, 298 (70.6%) had at least one medicine stopped with 704 medicines being stopped. This represented 19.5% of the medicines originally prescribed (3602 medicines). There was no statistically significant difference between pharmacist only and pharmacist plus GP in terms of stopping medicines. The main groups of medicines stopped were laxatives, skin products and bone protection. There was weak correlation between the original number of medicines prescribed and the number stopped. Conclusions: This study has shown that medicines optimisation reviews can lead to a reduction in polypharmacy for care home residents through a deprescribing process. Patients' medicine regimens were simplified and optimised while making financial significant savings for the National Health Service.